Efficacy of the Bushen Jianpi Huoxue Formula on Beclin-1/Bcl-2-mediated autophagy and apoptosis in osteoblasts - Lin, Yanping; Zhao, Rui; Huang, Jiachun; Chen, Tongying; Yang, Haolin; Guo, Haiwei; Wan, Lei; Zhang, Zhihai; Li, Ying; Zhu, Genfu; Huang, Hongxing (Frontiers in Pharmacology, 2025)
BackgroundThe Beclin-1/Bcl-2 complex plays a pivotal role in regulating both autophagy and apoptosis in osteoblasts affected by osteoporosis. This study first investigates whether the Bushen Jianpi Huoxue Formula can enhance the cellular function of osteoblasts. Additionally, it initially explores the functional mechanism of Beclin-1/Bcl-2-related apoptosis.MethodsOsteoblasts were isolated from the calvaria of three-day-old Sprague-Dawley female rats. The lyophilized power of the Bushen Jianpi Huoxue Formula was prepared from the following ingredients: Fructus Psoraleae, Epimedii Folium, Desertliving Cistanche, Prepared Rehmannia Radix, Radix paeoniae alba, Astragali Radix, Semen Cuscuta, Radix Salviae miltiorrhizae, Angelica sinensis, and Jujube. The primary components were detected by HPLC-MS. Beclin-1 overexpressed osteoblasts were constructed by transfection. Gene expression and protein level were examined by qRT-PCR and immunoblotting assay. Cell viability, apoptosis, and autophagy were assayed with CCK-8, flow cytometer, MDC staining, and Lyso-Tracker staining, respectively. Osteogenic differentiation was assayed by ALP staining, and mineralization by ARS staining. The complex of Beclin-1/Bcl-2 was detected by immunoprecipitation.ResultsThe results of this study indicated that the Bushen Jianpi Huoxue Formula could enhance both the proliferative activity, differentiation and mineralization of osteoblasts induced by Beclin-1 overexpression. This may be related to its role in activation of the WNT/β-CATENIN by increasing protein expression of WNT1 and β-CATENIN more than 1-fold. The formula effectively inhibited autophagy rate and apoptosis rate of osteoblasts by 50%. Furthermore, the formula was effective in attenuating endoplasmic reticulum stress by decreasing protein expression of AFT4, CHOP, eIF2α, and GRP78 more than 50%, which may play functions by suppressing the PERK signaling pathway. However, Mif treatment significantly weakened the effects of the formula.ConclusionBushen Jianpi Huoxue Formula effectively enhanced the osteogenic activity by inhibiting Beclin-1-induced autophagy instead of the binding of Beclin-1 and Bcl-2. This underscores the formula’s multifaceted role in promoting bone health and managing cellular stress, and offers novel insights into its therapeutic potential against osteoporosis.